(re)Constructing the way we build - Skills Development Centre in Delft - Soeker, Imaad (School of Architecture, Planning and Geomatics, 2023)
Identity can be associated with a person, group or place and is defined as the sense of belonging. Thus, a person who doesn't belong and an architecture of placelessness both lack an identity. It can be shaped by history or by the current day. This design dissertation proposes a more situated architectural identity by exploring the relationship between the social and the material in Delft, Cape Town. The strong themes of the temporary and the permanent and formal and informal create a conflict of identity within Delft. The theory of Critical Regionalism will be the foundation for creating an architecture of identity within the context of Delft. An architecture of place will be achieved by being critical of the context and current construction practices and making use of readily and locally sourced materials. Sandbag construction and local vernacular practices will be combined to create an architecture of permanence, place, and identity within Delft. This design dissertation tests these themes through the speculative design of a Skills Centre, as there is a strong culture of making and learning within Delft. The Skills Centre will revolve around the idea of making, from alternative construction to the growth and preparation of food. The main concept of the Skills Centre is to act as a catalyst in the upskilling of the community and thus create a new identity for them. The Skills Centre will embed itself within the concept of a circular economy through construction and operation. Sandbag construction will act as the first economic driver; once the Skills Centre is completed, it will act as a catalytic economic driver. Creating an architecture of permanence that is rooted in place should start creating a positive identity and sense of belonging within Delft.